Social and Psychological Determinants of Emotion Regulation in Adolescents - Ningrum, Luh De Kusuma (Yayasan Sinergi Kawula Muda, 2023)
Adolescence is a critical developmental stage characterized by emotional and social challenges that significantly impact mental health. Emotion regulation plays a fundamental role in adolescent well-being, influencing behavioral outcomes, peer relationships, and resilience to stress. This study reviews existing literature on emotion regulation among adolescents, examining factors such as social support, peer victimization, and family influence. A systematic literature search was conducted using Scopus, PubMed, and Google Scholar, focusing on studies that explore emotion regulation interventions and their effectiveness. Findings indicate that strong emotion regulation skills act as protective factors against maladaptive behaviors, while poor regulation is associated with increased risks of anxiety, depression, and self-injury. Social support from family and peers plays a crucial role in shaping adolescent emotional development, with parental responsiveness and peer interactions significantly influencing regulatory abilities. Interventions such as mindfulness-based programs and cognitive behavioral therapy demonstrate effectiveness in enhancing emotion regulation, but their success depends on cultural and contextual adaptations. Additionally, systemic factors, including educational policies and social environments, further influence emotion regulation outcomes. The study emphasizes the need for integrated intervention strategies that address individual, familial, and societal influences on emotion regulation. Future research should investigate long-term intervention impacts, explore the neurobiological basis of emotion regulation, and develop culturally adapted programs to enhance effectiveness. Implementing evidence-based approaches in schools and communities can significantly improve adolescent mental health and resilience.